ANALISIS PENGGUNAAN APLIKASI FUZZY ANALYTICAL HIERARCHY PROCESS DALAM SELEKSI KARYAWAN - Yesi Yusmita; Aris Fiatno (Jurnal Teknik Industri Terintegrasi, 2018)
This study discusses the problem of decision making to choose the best employee alternatives. To solve this problem Fuzzy Analytical Hierarchy Process is used, the development of conventional Analytical Hierarchy Process which is designed to deal with problems with more subjective criteria. The choice of the best employees with the Fuzzy Analytical Hierarchy Process shows that the subjectivity of the criteria is of greater concern compared to using the conventional Analytical Hierarchy Process.